Efektivitas Model Explicit Intstruction (Pembelajaran Langsung) Terhadap Kemandirian Pengobatan Luka Lecet Bagi Anak Tunagrahita Ringan Kelas V SLB Perwari Kota Padang - Yani Adriana; Kasiyati Kasiyati (Inovan Publisher, 2025)
This study was motivated by problems found at SLB Perwari Padang in children with mild intellectual disabilities. The problem encountered by the researcher was that there was a child who could not treat his wounds independently, even though the wounds suffered by the child were minor. The purpose of this study was to prove that the explicit instruction learning model is effective for teaching children with mild intellectual disabilities to treat minor wounds independently. The method used in this study was the Single Subject Research (SSR) method with an A-B-A design. A1 was the initial condition of the child before the intervention, B was the intervention, and A2 was the condition after the intervention was no longer given. Baseline 1 (A1) was conducted over 6 meetings until stable data was achieved, with data stability found in meetings 4 to 6. The intervention through the direct learning model (B) was conducted over 6 sessions until the data stabilized, with data stability found in sessions 10 to 12, and the second baseline (A2) was conducted over 4 sessions to see if there was any effect of the intervention on the ability to treat abrasions, with data stabilization found in sessions 13 to 16. The data collection techniques used were observation, documentation, and testing. The results of the study showed that the direct learning model was effective for the independence of treating abrasions in children with mild intellectual disabilities.